Delito de online grooming: el análisis del groomer y su modus operandi = Online grooming : a case study of groomers and their modus operandi - Bautista, Isabel Matthews (International e-journal of criminal sciences, 2024)
Among all the forms of online victimization that are likely to harm minors, the one that is most concerning, due to its physical and psychological consequences, is the victimization of sexual crimes, hence the relevant role of online grooming. The present research work aims to elaborate a criminological profile of the potential perpetrators of the crime at issue through a content analysis of 107 real conversations in English between groomers and fake minors as well as 20 Spanish sentences. The results obtained revealed that the profile of the potential groomer is as follows: a male with an age ranging from 18 to 49 years old who is mainly looking for girls between 13 and 15 years old. Apart from the welcoming, affectionate-intimate, cautious, deceptive, and aggressive conduct, it was observed that most of them had an exclusively sexual behavior, resembling the classification of the hyper-sexualized groomer of the scientific literature.